2010
DOI: 10.1108/07363761011086326
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Chinese youth consumers' acceptance of mobile marketing

Abstract: Purpose -The purpose of this paper is to examine factors affecting consumers' acceptance of mobile marketing in China. Design/methodology/approach -The authors draw on technology acceptance and uses and gratifications theories to develop a conceptual model of antecedent factors (including risk acceptance related to the mobile platform and personal attachment related to mobile devices) and marketing-related and value-based mobile activity related to the acceptance of mobile marketing practice. The conceptual mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 40 publications
(64 reference statements)
1
69
0
1
Order By: Relevance
“…Studies in other countries found an immense potential of mobile advertising to succeed in conjunction with high penetration and subscriptions rate (Adham, et al, 2008;Basheer & Ibrahim, 2010;Beneke, Cumming, Stevens, & Versfeld, 2010;Friedrich, Grone, Holbling, & Peterson, 2009;Gao, Sultan, & Rohm, 2010;Jayawardhena, Kuckertz, Karjaluoto, & Karjaluoto, 2009;Kim, Heo, & Chan-Olmsted, 2010;Laszlo, 2009;Merisavo et al, 2010). The widespread of various telecommunication devices for communication purposes have changed the nature, reach, velocity and locus of individual's behavior (Bandura, 2001;Mort & Drennan, 2007;Muk, 2007;Ratten & Ratten, 2007).…”
Section: The Significance Of the Studymentioning
confidence: 99%
“…Studies in other countries found an immense potential of mobile advertising to succeed in conjunction with high penetration and subscriptions rate (Adham, et al, 2008;Basheer & Ibrahim, 2010;Beneke, Cumming, Stevens, & Versfeld, 2010;Friedrich, Grone, Holbling, & Peterson, 2009;Gao, Sultan, & Rohm, 2010;Jayawardhena, Kuckertz, Karjaluoto, & Karjaluoto, 2009;Kim, Heo, & Chan-Olmsted, 2010;Laszlo, 2009;Merisavo et al, 2010). The widespread of various telecommunication devices for communication purposes have changed the nature, reach, velocity and locus of individual's behavior (Bandura, 2001;Mort & Drennan, 2007;Muk, 2007;Ratten & Ratten, 2007).…”
Section: The Significance Of the Studymentioning
confidence: 99%
“…Two theoretical perspectives, the technology acceptance model (TAM) and the uses and gratifications theory (UGT), have been applied extensively in the study of consumer behavior related to the adoption and use of technology (Chua, Goh, & Lee, 2012;Gao, Sultan, & Rohm, 2010;Stafford, Stafford, & Schkade, 2004). For instance, a recent study by Kim et al (2009) provided empirical evidence supporting the integration of TAM (Davis, 1989) and the theory of reasoned action (Fishbein & Ajzen, 1975) in the mobile communication context.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Examining these personal traits is also theoretically grounded on UGT , which has been used to explain the role of personal motive related to consumer choice of a new communication medium (Chua et al, 2012;Gao et al, 2010;Stafford et al, 2004).…”
Section: Stimulus-organism-response (S-o-r) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferris analizó las propiedades de utilizar el móvil como herramienta de comunicación, revelando que permitía (Ferris, 2007): (a) potenciar la interactividad, (b) utilizar bases de datos de potenciales clientes, (c) comprender mejor a los consumidores utilizando el data mining (minería de datos), (d) dirigir campañas concretas a targets muy específicos de clientes, (e) medir la eficacia de dichas campañas y (f) estudiar sus posibilidades como medio de pago. Varnali y Toker (2010) realizan una excelente revisión sobre las investigaciones realizadas hasta la fecha en este ámbito, y cada vez aparecen más estudios que atienden a categorías de productos concretas (Shankar, Venkatesh, Hofacker, y Naik, 2010), o a las diferencias interculturales (Gao, Sultan, y Rohm, 2010).…”
Section: Revisión Teóricaunclassified